Production of extracellular silver nanoparticles by radiation-resistant Deinococcus wulumuqiensis R12 and its mechanism perspective - Xiao, Anqi; Wang, Bixuan; Zhu, Liying; Jiang, Ling (Process biochemistry (1991), 2021)
[Display omitted] •Spherical silver nanoparticles of uniform size were synthesized by Deinococcus wulumuqiensis R12.•R12 strain could tolerate a high concentration of silver nitrate when synthesizing AgNPs.•A NADPH-dependent oxidoreductase was identified to synthesize AgNPs in R12 strain. Recently, rapid progress has been made in the utilization of microbes for green synthesis of metal nanoparticles. We found that the cell-free supernatant of the extremophile Deinococcus wulumuqiensis R12 contains silver nanoparticles (AgNPs) when grown in media with different concentrations of AgNO3. The microbially synthesized AgNPs were then systematically characterized by UV/Vis spectroscopy (UV/Vis), X-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive spectroscopy (EDS), dynamic light scattering (DLS) and zeta potential measurements. The microbial AgNPs had an absorption peak at 430 nm and had a face-centered cubic structure. They were spherical with a uniform size of 5–16 nm, which was smaller than most reported AgNPs. The mechanism of nanoparticle synthesis by D. wulumuqiensis R12 was then briefly investigated. A previously unknown NADPH-dependent oxidoreductase of 28.29 kDa was identified, which might play the main role in the biosynthesis of AgNPs by strain R12. The concentration of the oxidoreductase in the supernatant increased 4-fold after the addition of AgNO3. Furthermore, the addition of NADPH significantly improved the production of AgNPs.